Neonatal liver failure owing to gestational alloimmune liver disease without iron overload. Issue 5 (29th July 2014) - Tsunoda, Tomoyuki; Inui, Ayano; Kawamoto, Manari; Sogo, Tsuyoshi; Komatsu, Haruki; Kasahara, Mureo; Nakazawa, Atsuko; Fujisawa, Tomoo
Abstract : Although neonatal hemochromatosis (NH) is a well‐known cause of liver failure during the neonatal period and iron deposition in extrahepatic tissues is considered essential in the diagnosis of NH, there is no consensus regarding the pathology or diagnostic criteria of NH. Recent studies of immunohistochemical assays have shown that the C5b‐9 complex (the terminal membrane attack complement complex) is strongly expressed in the liver of NH cases, suggesting that a gestational alloimmune mechanism is the cause of liver injury. The patient was a low birthweight primiparous male born at 37 weeks of gestation by vaginal delivery. Blood tests 3 h after birth showed signs of liver failure, including high transferrin saturation, resembling the clinical characteristics of NH. However, magnetic resonance imaging and a lip biopsy showed no obvious iron deposition outside the liver. The patient was refractory to exchange transfusion and immunoglobulin therapy but was successfully treated by liver transplantation. Histologically, the explanted liver showed established cirrhosis, with large amounts of human C5b‐9 in the residual hepatocytes, suggesting the alloimmune mechanism of liver injury was the cause of his liver failure. Liver failure caused by a gestational alloimmune mechanism should be considered in patients with antenatal liver failure, even without obvious extrahepatic siderosis.